Prevalence of psychoactive substance use by adolescents in public schools in a municipality in the São Paulo Metropolitan Area, Brazil - Eliana Pereira Vellozo; Maria Sylvia de Souza Vitalle; Maria Aparecida Zanetti Passos; Sheila Rejane Niskier; Teresa Helena Schoen; Peter Richard Hall; Francisco Plácido Nogueira Arcanjo; Roberto Fernandes da Costa; Benjamin Israel Kopelman; Tulio Konstantyner (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
This study aimed to estimate the prevalence of psychoactive substance use by adolescents from public schools. This is a cross-sectional study that used a random sample of adolescents from five public schools located in a municipality in the central-west region of the São Paulo Metropolitan Area, Brazil. Information on demographic, socioeconomic, and drug use was collected using self-report questionnaires. The sample consisted of 1,460 students, 716 (49%) males, aged 10-19 years (13.19±2.04 years). The prevalence of psychoactive substance use in the last month was 51% for analgesics; 48.8% for alcohol; 37.3% for tobacco; 30.8% for tranquilizers; 23.1% for marijuana; 22.6% for anabolic steroids; 21.6% for ecstasy; 15.3% for amphetamines/stimulants; 13.4% for phencyclidine; 12.9% for cocaine/crack; 12.6% for inhalants/solvents; 11.5% for opiates; 11.4% for hallucinogens; and 16.2% for other unclassified drugs. Elementary and middle school students were more likely to consume tobacco (OR = 2.306; 95%CI: 1.733-3.068; p < 0.001), and male students were more likely to consume any type of substance. We identified a high use of psychoactive substances among this study participants, with a higher prevalence among male students.